Alive in the nuclear age vol.1 . ([Ottawa] National Film board of Canada)
An interview with Canadian and Soviet youths about nuclear weapons, Japanese who experienced the Hiroshima bombing, etc. it also presents footages on World War I and II, invention of the first atomic bomb and Canada's nuclear technology.
1.What Canadian youth are saying -- 2.What Soviet youth are saying -- 3. The road to total war -- 4.The first atomic bombs -- 5. No more Hiroshima -- 6.Canada's nuclear technology.
VHS
Keywords: nuclear energy